Victimological research in Slovenia - Šelih Alenka (Temida, 2012)
The article gives an overview of victimological research in Slovenia. The overview has different orientations: it started with analysis of the victim’s role in commission of the offence and ended with research on help and support to the victim; it started with research into particular offences and their victims and proceeded to analyses of structural violence. Victim surveys as having been implemented in Slovenia are being presented. The article follows the victimological research studies from first empirical projects to those studies that have later allowed for theoretical generalizations. The contribution gives an account of activities of victimology as an advocacy as well as of victim support schemes developed in Slovenia during the last ten to twenty years. Finally, it presents the development of the concept of restorative justice, especially mediation and the ways it has entered into the Slovene criminal justice system.